2020
DOI: 10.1111/myc.13143
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic cut‐off value for Aspergillus fumigatus‐ and flavus‐specific IgG with clinical relevance in chronic pulmonary Aspergillus infection: A pilot study in Taiwan

Abstract: Background The diagnostic cut‐off value for chronic pulmonary Aspergillosis (CPA) by Aspergillus fumigatus‐specific IgG has never been evaluated In Taiwan. The cut‐off value for Aspergillus flavus‐specific IgG has not been evaluated worldwide. Objectives Evaluate diagnostic cut‐off value of Aspergillus IgG and its application characteristics. Patients/Methods Blood from control groups and treatment‐naïve patients with CPA infections was collected for Aspergillus‐specific IgG measurements. Controls were patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Among them, ImmunoCap Asp-IgG is one of the most commonly used kits with good performance. For ImmunoCap Asp-IgG, different cut-off points have been proposed, ranging from 20 to 50 mgA/L [13][14][15][16]. Table 2 summarizes previous reports and the performance of their proposed cut-off points in original and current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, ImmunoCap Asp-IgG is one of the most commonly used kits with good performance. For ImmunoCap Asp-IgG, different cut-off points have been proposed, ranging from 20 to 50 mgA/L [13][14][15][16]. Table 2 summarizes previous reports and the performance of their proposed cut-off points in original and current study.…”
Section: Discussionmentioning
confidence: 99%
“…This raises concerns whether Asp-IgG could be used for diagnosing CPA in this setting and an optimal cut-off level is also not readily available. Furthermore, previous studies determining the cut-off level of Asp-IgG were mainly conducted with retrospective design, using cases from CPA databases and healthy control [13][14][15][16]. Prospective studies in a real-world clinical setting were scant and multicenter recruitment as well as validation was also lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In CCPA, the Th2 response is the main immune reaction, and the cytokines IL4, IL5, IL-15, TNF-α, and IL-10 were increased in peripheral blood [27]. One study showed that IL-1B in peripheral blood was associated with disease activity in CPA, and disease activity was evaluated by visual methods and by changes in the CCPA in chest images [25]. One case series showed that the administration of IFN-γ had a protective role in preventing invasive fungal infection; however, its downstream cytokine expression was not comprehensively evaluated [24].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, lung fibrosis and collagen deposits are usually observed surrounding fungal hyphae [21]. Biomarkers, such as CRP, ESR, fibrinogen [22], TNF-α, IL-6, IL-8 [23], IFN-γ [24], and IL-1B [25], have been correlated with disease activity or treatment response in pulmonary aspergillosis patients.…”
Section: Introductionmentioning
confidence: 99%
“…CPA was defined according to national guidelines. 21 The cut-off value for Aspergillus fumigatus IgG was applied according to our previous study, 22,23 and Aspergillus niger IgG was determined according to the manufacturer's suggestion. Patients with a blood sample positive for A. fumigatus or A. niger IgG with coexisting abnormal chest imaging findings and clinical symptoms fulfilling the CPA criteria 21 were diagnosed with CPA.…”
Section: Materials S and Me Thodsmentioning
confidence: 99%